THE GREEN REVOLUTION TECHNOLOGY AND ITS IMPACT IN THE SOCIO ECONOMIC LIFE OF INDIA - Singha, Sutandra (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
The Green Revolution technology was introduced to India in the 1960s to address the issue of food shortages. This technology involved bio-engineered High Yielding Varieties (HYV) seeds that worked in conjunction with chemical fertilizers and extensive irrigation to increase crop yields. Use of pesticides and insecticides, double cropping, land reforms, Command Area Development (CAD), consolidation of holdings, development of rural infrastructure, farm mechanization, the supply of agricultural credit and setting up agricultural universities are additional characteristics of India’s green revolution. Green Revolution has influenced the socio-economic life in India to a significant extent as is evident in terms of increase in agricultural production, prosperity among farmers, self-sufficiency in food grains, capitalistic farming, plowing back of profits, agro-industrial growth and rural employment. However, poor farmers who could not participate in this capital intensive technology followed by widening income gaps between social classes. Heavy use of pesticides and chemical fertilizers caused some serious health problems. Recently, recurrent spells of shortages in some essential food items, increasing pressure of population on the available food stock, shrinking of agricultural land due to urban industrial development and erratic climatic behavior are paving the way of food scarcity and inflation. Sadly, there has been no significant research in this regard. In this context, this paper discusses the past and present scenario regarding the impact of Green Revolution technology on India’s economy and society. Concluding remarks suggest certain policies and practicable measures aimed to provide long-term food security to the nation.